DAMPAK KEPEMILIKAN MANAJERIAL, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN EMITEN RETAIL TRADE YANG LISTED DI BURSA EFEK INDONESIA - Iwan Kusuma Negara; I Dewa Gde Bisma (Master of Management, Mataram University, 2021)
This research aims to analyze the effect of managerial ownership, capital structure, and profitability on firm value. Capital structure is proxied by Debt to Equity Ratio (DER), and Profitability is proxied by Return on Asset (ROA). Meanwhile, firm value is proxied by Price to Book Value (PBV). Data were analyzed by multiple regression analysis. The population consists of 20 firms that were listed in Retail trade sector of Indonesian Stock Exchange in the period of 2013 – 2017. There are 6 firms (30 observation data) are chosen as sample of the study. The findings show that managerial ownership, DER, and ROA have positive and significant effect on firm value.Keywords :Firm value, PBV, Managerial ownership, Capital structure, DER, Profitability, ROA.